2014
DOI: 10.1016/j.acra.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasonic Histogram Features to Evaluate Radiation Toxicity of the Parotid Glands

Abstract: Rationale and Objectives To investigate the diagnostic accuracy of ultrasound histogram features in the quantitative assessment of radiation-induced parotid gland injury and to identify potential imaging biomarkers for radiation-induced xerostomia (dry mouth)—the most common and debilitating side effect after head-and-neck radiotherapy (RT). Materials and Methods Thirty-four patients, who have developed xerostomia after RT for head-and-neck cancer, were enrolled. Radiation-induced xerostomia was defined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…SD values also increased from time point 2 to 3, indicating more heterogeneity due to fibrosis and repair of parotid glands four months after radiotherapy [ 23 ]. Yang et al also reported that the 3-dB bandwidth further widened from acute toxicity (with 3 months after radiotherapy) to late toxicity of parotid glands (beyond 3 months after radiotherapy), indicating a more heterogeneous texture of parotid parenchyma [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…SD values also increased from time point 2 to 3, indicating more heterogeneity due to fibrosis and repair of parotid glands four months after radiotherapy [ 23 ]. Yang et al also reported that the 3-dB bandwidth further widened from acute toxicity (with 3 months after radiotherapy) to late toxicity of parotid glands (beyond 3 months after radiotherapy), indicating a more heterogeneous texture of parotid parenchyma [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al took an additional step to quantitatively model sonogram images to identify patients with acute versus late toxicities. 85…”
Section: Side Effects and Therapeutic Intervention Of Radiation-inducmentioning
confidence: 99%
“…Computed tomography (CT) can show morphological changes of the parotid glands after radiotherapy, but CT brings additional radiation exposure (8,9). Ultrasonography (US) can also been used to evaluate radiation-induced parotid damage, yet US depends on the settings of the scanner and the experience of the operator (8,10). Magnetic resonance imaging (MRI) presents an ideal modality to evaluate radiation-induced parotid damage due to its excellent soft tissue contrast (11).…”
Section: Introductionmentioning
confidence: 99%